Immunology and Oxidative Stress in Multiple Sclerosis: Clinical and Basic Approach - Genaro G. Ortiz; Fermín P. Pacheco-Moisés; Oscar K. Bitzer-Quintero; Ana C. Ramírez-Anguiano; Luis J. Flores-Alvarado; Viridiana Ramírez-Ramírez; Miguel A. Macias-Islas; Erandis D. Torres-Sánchez (Clinical and Developmental Immunology)
Multiple sclerosis (MS) exhibits many of the hallmarks of an inflammatory autoimmune disorder including breakdown of the blood-brain barrier (BBB), the recruitment of lymphocytes, microglia, and macrophages to lesion sites, the presence of multiple lesions, generally being more pronounced in the brain stem and spinal cord, the predominantly perivascular location of lesions, the temporal maturation of lesions from inflammation through demyelination, to gliosis and partial remyelination, and the presence of immunoglobulin in the central nervous system and cerebrospinal fluid. Lymphocytes activated in the periphery infiltrate the central nervous system to trigger a local immune response that ultimately damages myelin and axons. Pro-inflammatory cytokines amplify the inflammatory cascade by compromising the BBB, recruiting immune cells from the periphery, and activating resident microglia. inflammation-associated oxidative burst in activated microglia and macrophages plays an important role in the demyelination and free radical-mediated tissue injury in the pathogenesis of MS. The inflammatory environment in demyelinating lesions leads to the generation of oxygen- and nitrogen-free radicals as well as proinflammatory cytokines which contribute to the development and progression of the disease. Inflammation can lead to oxidative stress and vice versa. Thus, oxidative stress and inflammation are involved in a self-perpetuating cycle.